Digital Taxation in Borderless Economy: A Critical Evaluation of OECD’s Pillars and Implications for Global Tax Equity (Journal of Asian Development Studies, 2025)
The development of a global, borderless digital economy has rendered the old international tax rules highly obsolete, and people around the globe are now demanding reform. The Organisation for Economic Co-operation and Development (OECD) subsequently proposed Pillar One and Two as a means of redistributing taxing rights and developing a global minimum corporate tax rate. The proposals in this study are critically assessed in a qualitative, exploratory, and comparative manner using both document analysis and expert interviews in selected jurisdictions. The results indicate that Pillar Two has garnered significant support, particularly among OECD member countries, with ECDs that are relatively transparent in their structure and have a profit-boosting nature. Contrastingly, Pillar One has stagnated due to the complicated treaty requirements and political opposition, at least in the United States and other leading economies. Although there is a vast potential for generating world revenue through Pillar Two, projected at between $155 billion and $ 192 billion annually, it favours the residence jurisdictions disproportionately. It leaves many developing nations disadvantaged. These reforms are restricted in access and impact for low-income states due to administrative complexity, inadequate technical capacity, and insufficient equity mechanisms. The study concludes that unless the voice of the Global South is represented successfully and more emphasis is placed on sharing revenues equally, the proposals offered by the OECD will threaten to perpetuate the current differentiation in the global taxation system. Some of the suggestions include widening the scope of Pillar One, enhancing the Subject to-tax Rule, and building capacity in developing countries.